2016
DOI: 10.1021/acs.langmuir.5b04069
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Tetraphenyldibenzoperiflanthene (DBP) Films on Ag(111) in the Monolayer Regime

Abstract: Tetraphenyldibenzoperiflanthene (DBP) is a promising candidate as a component of highly efficient organic photovoltaic cells and organic light-emitting diodes. The structural properties of thin films of this particular lander-type molecule on Ag(111) were investigated by complementary techniques. Highly ordered structures were obtained, and their mutual alignment was characterized by means of low-energy electron diffraction (LEED). Scanning tunneling microscopy (STM) images reveal two slightly different arrang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
45
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(54 citation statements)
references
References 38 publications
8
45
1
Order By: Relevance
“…A comparison with reported lateral structures of DBP on Ag(111) [ 34 ] and Au(111) [ 33 ] shows very similar adsorbate lattice parameters except for the unit cell rotation with respect to the primitive substrate vector (see Table 1 ). For this reason, we find that the molecules adopt a similar herringbone arrangement (rectangular unit cell with a basis of two molecules with different azimuthal orientation) on h-BN/Ni(111).…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…A comparison with reported lateral structures of DBP on Ag(111) [ 34 ] and Au(111) [ 33 ] shows very similar adsorbate lattice parameters except for the unit cell rotation with respect to the primitive substrate vector (see Table 1 ). For this reason, we find that the molecules adopt a similar herringbone arrangement (rectangular unit cell with a basis of two molecules with different azimuthal orientation) on h-BN/Ni(111).…”
Section: Resultsmentioning
confidence: 67%
“…In the case of highly ordered DBP on h-BN/ Ni(111), suitable coincidences with the lowest substrate orders are the on-line coincidences (1, 2), (−1, −2), (−2, 1), and (2, −1). [34]. The angle Γ is defined between the lattice vectors of the adsorbate and .…”
Section: Lateral Structurementioning
confidence: 99%
“…An important prerequisite for vibrational progression to occur is the presence of sharp molecular resonances and, thus, the extended lifetime of the transient charge state of the molecule [54], which is fulfilled here owing to the weak DBP-metal hybridization [39,55]. The peaks n ± (n ≥ 1) are not due to other molecular orbitals since calculations of the free molecule revealed that the HOMO−1 (LUMO+1) is 1 eV below (above) the HOMO (LUMO) energy [53].…”
Section: Resultsmentioning
confidence: 80%
“…The optimized structure was obtained by density functional calculations at the B3LYP/6 − 311G++(d,p) level. 44 The energy of the weak fluorescence peak at 2.28 eV (ε), which was not reported in the absorption experiments, 45 is compatible with light emission from non-thermalized excitons, a photon emission process that is generally referred to as hot electroluminescence where vibrationally excited states of S 1 relax to the vibrational ground state of S 0 , i. e., The Purcell effect (vide supra) entails a strong reduction of the fluorescence lifetime in plasmonic environments. Similar observations of luminescence peaks blue-shifted from the S 1 (ν = 0) −→ S 0 (ν = 0) transition were reported from multilayers of phthalocyanines 21…”
mentioning
confidence: 99%